2022
DOI: 10.1123/japa.2020-0391
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Home-Based Exercise Snacking and Tai Chi Snacking Delivered Remotely to Self-Isolating Older Adults During COVID-19

Abstract: The purpose of this study was to examine the feasibility and acceptability of remotely delivered, home-based exercise programs on physical function and well-being in self-isolating older adults during the COVID-19 pandemic. In a four-arm randomized controlled trial, 63 participants (aged 65 years and older) were allocated to one of three home-based daily (2 × 10-min) exercise interventions (exercise snacking, tai chi snacking, and combination) or control (UK National Health Service Web pages). Functional asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 48 publications
6
36
0
Order By: Relevance
“…While the short-term duration of the exercise intervention also likely influenced the magnitude of any changes (or between group differences) in physical function, previous findings suggest similar pragmatic and unsupervised resistance exercise approaches can be effective for improving measures of physical function (e.g., 60-second sit-to-stand performance) after 4 weeks [ 17 ]. Nevertheless, our findings are consistent with another study [ 26 ] that also showed no difference in changes in physical function measures assessed remotely using videoconferencing after 4 weeks of twice-daily ‘exercise snacking’ versus controls. Longer-term studies in larger cohorts are therefore needed to confirm these preliminary findings and determine whether similar resistance ‘exercise snacking’ approaches, and potentially those incorporating additional exercise variety, both upper- and lower-body exercises, and external resistance (e.g., via resistance bands and/or small weights), are effective for improving physical function in older adults.…”
Section: Discussionsupporting
confidence: 92%
“…While the short-term duration of the exercise intervention also likely influenced the magnitude of any changes (or between group differences) in physical function, previous findings suggest similar pragmatic and unsupervised resistance exercise approaches can be effective for improving measures of physical function (e.g., 60-second sit-to-stand performance) after 4 weeks [ 17 ]. Nevertheless, our findings are consistent with another study [ 26 ] that also showed no difference in changes in physical function measures assessed remotely using videoconferencing after 4 weeks of twice-daily ‘exercise snacking’ versus controls. Longer-term studies in larger cohorts are therefore needed to confirm these preliminary findings and determine whether similar resistance ‘exercise snacking’ approaches, and potentially those incorporating additional exercise variety, both upper- and lower-body exercises, and external resistance (e.g., via resistance bands and/or small weights), are effective for improving physical function in older adults.…”
Section: Discussionsupporting
confidence: 92%
“…This demonstrates a need for technology that both supports users through such changes in motivation and facilitates low intensity exercise and breaks from excessive sedentariness, which has been shown to be detrimental to people's well-being and health (47). Prior systems have been shown to effectively motivate breaks from sedentariness through prompting and exercise snacking (51,52), which may be leveraged to support low intensity activity when motivation is low.…”
Section: Opportunities Specific To Staying Active During Life Disruptionsmentioning
confidence: 99%
“…Table 1 summarizes the key characteristics in the selected studies. Issuing countries included Australia [ 30 , 31 ], Greece [ 32 ], Spain [ 33 , 34 ], The Netherlands [ 35 ], Germany [ 36 ], United States of America [ 37 , 38 ], United Kingdom [ 28 , 39 ], China [ 40 ] and Taiwan [ 41 ]. A noticeable increase in the number of publications could be seen for 2021 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…In general, this review comprised a range of technologies and measures applied to the evaluation of adherence ( Table 1 ). The technologies used included computers [ 32 ], internet or websites [ 31 , 36 , 37 ], Amazon Alexa and internet [ 30 ], video platforms [ 33 , 38 , 39 ], and mobile applications [ 28 , 34 , 35 , 40 , 41 ]. See Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation